1993
DOI: 10.1002/polb.1993.090310201
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and properties of polycaprolactone‐poly(dimethyl siloxane)‐polycaprolactone triblock copolymers

Abstract: The molecular structure, crystallization, solid‐state morphology, thermal properties, and phase behavior of two copolymers consisting of a poly(dimethylsiloxane) (PDMS) mid‐block coupled to polycaprolactone (PCL) end‐blocks were investigated. Both copolymers (which differ only in the molecular lengths of the PCL end‐blocks) were found to be lamellar systems, whose core consists of PCL chains having the same crystal structure as PCL homopolymer, and whose amorphous interlayers contain the PDMS blocks and the PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 18 publications
4
26
0
Order By: Relevance
“…Lovinger et al determined average lamellar spacings of 15 and 18 nm by analysis of TEM micrographs and by SAXS, respectively. 8 Clearly the present results are in excellent agreement with these previous findings for bulk spacings.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Lovinger et al determined average lamellar spacings of 15 and 18 nm by analysis of TEM micrographs and by SAXS, respectively. 8 Clearly the present results are in excellent agreement with these previous findings for bulk spacings.…”
Section: Resultssupporting
confidence: 94%
“…Such spherulitic morphology is consistent with the studies by Lovinger et al of PCL-b-PDMS-b-PCL triblock copolymers with similar molecular weights and linker groups. 8 High magnification shows a lamellar morphology is present in which fibrous, PCL-rich semicrystalline spherulites are seen to be completely space filling with amorphous PDMS located in the interlamellar regions. Exact evaluation of interlayer thicknesses are made difficult by the lack of distinct, sharp boundaries that separate such layers; however, thicknesses measured using a ruler overlaid on the 1.00 µm phase image are estimated to be between 5 and 10 nm for bright regions and between 5 and 15 nm for dark regions.…”
Section: Resultsmentioning
confidence: 97%
“…[34][35][36] It has also been reported that the bending instability of polymeric jet is increased when solvents with high dielectric constant are used, resulting in an increased deposition area, the enlargement of the jet path favoring the reduction of fiber size. 37 XRD spectra showed the characteristic (110), (111), (200), and (210) reflections of the orthorhombic crystal structure of PCL, 16,38 as pictured in Figure 4. Thus, electrospinning of PCL seems not to induce significant modifications of its crystal structure.…”
Section: Discussionmentioning
confidence: 98%
“…15,16 PCL is a semicrystalline bio-resourceful poly(α-hydroxyester) with an orthorhombic crystal structure. 17,18 Due to its hydrophobic nature and high crystalline degree, PCL degrades slowly 19,20 by hydrolysis and has been considered in a wide range of applications, for example, biodegradable packaging materials, implantable biomaterials, scaffold, and micro-particles for drug delivery. [21][22][23] The crystallization behavior of PCL blends has been investigated in a number of studies.…”
Section: 12mentioning
confidence: 99%